THEISTIC EVOLUTION IN THREE TRADITIONS: with Willem B. Drees, "Naturalism and Religion: Hunting Two Snarks?"; Ursula W. Goodenough and Jeremy E. Sherman, "The Emergence of Selves and Purpose"; Matthew D. MacKenzie, "Spiritual Animals: Sense‐Making, Self‐Transcendence, and Liberal Naturalism"; Curtis M. Craig, "The Potential Contribution of Awe and Nature Appreciation to Positive Moral Values"; Mark E. Hoelter, "Mysterium Tremendum in a New Key"; Charles W. Fowler, "The Convergence of Science and Religion"; Todd Macalister, "Naturalistic Religious Practices: What Naturalists Have Been Discussing and Doing"; Paul H. Carr, "Theologies Completing Naturalism's Limitations"; James Sharp, "Theistic Evolution in Three Traditions"; Alessandro Mantini, "Religious Naturalism and Creation: A Cosmological and Theological Reading on the Origin/Beginning of the Universe"; and Willem B. Drees, "When to Be What? Why Science‐Inspired Naturalism Need Not Imply Religious Naturalism." (Zygon: Journal of Religion & Science, 2021)
This article examines the role of theistic evolution in the work of three scholars: Christian theologian Keith Ward, rabbi and philosopher Jonathan Sacks, and Muslim physicist Nidhal Guessoum. Ward presents theistic evolution in a theological context, while Sacks and Guessoum present theistic evolution in broader contexts: Sacks as part of a reassessment of science and religion in western cultures, and Guessoum in arguing for a more sophisticated approach to science and religion within Islam. Their presentations of theistic evolution show the potential for theological and philosophical work concerning science and religion aimed at a popular audience which moves beyond the stubborn categories of conflict and independence or isolation.